Models of democracy and political spaces: the case of participatory democracy - Azevedo, Daniel Abreu (Geografares, 2018)
The main objective of this article is to bring the concept of political space and its relation to the democratic political system, specifically analyzing the case of Municipal Councils and the model of participatory democracy. From this theoretical-conceptual discussion, we seek to highligh, through a geographical perspective, the form of government that, at the same time it expands in the world, also it has its legitimacy questioned. Based on empirical research developed in the Municipal Councils of Rio de Janeiro between the years 2015-2016, the article specifically analyzes the case of the Tutelary Councils and the democratic legitimacy of these new Brazilian institutions.Keywords: political space, participatory democracy, Municipal Councils, Tutelary Councils, Rio de Janeiro.